Pendidikan di Masa Pandemi Covid-19 (Pemanfaatan Information Communication and Technology) - Jumiati Jumiati (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2021)
The era of the industrial revolution 4.0 brings challenges for educators to improve learning. In the 21st century learning framework requires easy generations to have skills and knowledge in the field of technology. Especially during the current covid-19 pandemic,itrequirs generations to utilize Information Technology and Communication in the learning proces. This study aims to discuss issues realated to the use of Information and Communication Technology in improving education in the era of the Covid-19 pandemic. The research methodology used is a qualitative research type through library research which is interpreted to produce information in the form of knowledge.The results of the discussion of this research show that Information and Communication Thechnology has a major influence in the era of the Covid-19 pandemic. The Ministry of Education issues a policy with distance learning (online) with the From Work Home System. Information and Communication Technology has several benefits including:(1) increasing student motivation;(2) Gaining insight from the horizon of thinking;(3) Fostering a spirit of togetherness;(4) Effektive and efficient digital portfolios;(5) Being a measuring tool used at school. The application in the online learning process are: Zoom application,google Hangouts application,whatsapp application,teacher room application,zenius learning application, and e-learning application.Learning media used to improve distance learning process (online) such as:internet,e-learning,e-mail,PowerPoint, and learning CDs. By utilizing learning media and application like this,it is easy for generations to have skills and abilities in terms of using and utilizing Information anf Communication Technology properly.